2020
DOI: 10.3390/ijerph17165757
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Anxiety and Factors Related to the COVID-19 Pandemic: An Exploratory Study Using the Children’s Anxiety Questionnaire and the Numerical Rating Scale

Abstract: The repercussions of the COVID-19 pandemic on children’s lives deserve attention. This study aimed to assess the prevalence of anxiety among Brazilian children and its associated factors during social distancing during COVID-19. We used a cross-sectional design with an online survey from April to May 2020 in Brazil. We included children aged 6–12 years and their guardians. The Children’s Anxiety Questionnaire (CAQ; scores 4–12) and the Numerical Rating Scale (NRS; scores 0–10) were used to measure anxiety. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 37 publications
7
134
1
10
Order By: Relevance
“…Garcia de Avila et al [ 14 ] found that 21.8% of children aged 6–12 years suffered from anxiety, out of the 289 participants in an online cross-sectional survey reported by guardians. Anxiety was higher among children having parents with essential jobs and those who were social distancing without parents, more persons living together in the home, and lower education level of guardians.…”
Section: Resultsmentioning
confidence: 99%
“…Garcia de Avila et al [ 14 ] found that 21.8% of children aged 6–12 years suffered from anxiety, out of the 289 participants in an online cross-sectional survey reported by guardians. Anxiety was higher among children having parents with essential jobs and those who were social distancing without parents, more persons living together in the home, and lower education level of guardians.…”
Section: Resultsmentioning
confidence: 99%
“…Forty five studies (63%) were high-quality (eTables 3 to 7); 23 cohort studies, 22-44 17 cross-sectional, 46,48,52,54,56,59,61,62,64,65,67,71-74,76,78 4 pre-post, 82,83,91-93 and 1 modelling study. 94 Eighteen (25%) were medium-quality; 13 cross sectional, 49-51,53,55,57,58,60,66,68,70,75,77 and 5 pre-post studies. 85,86,88-90 Nine (13%) were low-quality; 1 cohort, 45 3 cross sectional, 47,63,69 and 5 pre-post studies 79-81,84,87…”
Section: Resultsmentioning
confidence: 99%
“…High levels of depressive and anxiety symptoms were recently replicated by Duan et al [ 20 ]. Two non-representative studies from India with children and adolescents aged 5–18 years [ 21 , 22 ] and one study from Brazil with children and adolescents from 6 to 12 years [ 23 ] underline the negative impact of the pandemic on the mental health of children. They found that children and adolescents experienced severe psychological distress such as worries, helplessness, anxiety and fear.…”
Section: Introductionmentioning
confidence: 99%